Antihypertensives and COVID-19: Literature review (Research, Society and Development, 2021)
Hypertensive patients with COVID-19 are susceptible to complications of the disease, so this study aimed to analyze the action of drugs that act on Angiotensin (TA) in the presence of COVID-19 in comparison with other antihypertensives, as well as to identify the main ones. evidence on the subject presented so far. It is an integrative literature review containing 34 articles selected according to the inclusion criteria, between January / 2020 to February / 2021, in the PubMed, Embase, Scopus and Web of Science databases. The results do not show a causal relationship between the increase in COVID-19 infection and the use of RAAS inhibitors, but a possible protective effect of these against the severe manifestation of the disease due to the inhibition of the pro-inflammatory diseases of AT II. Thus, about ⅔ of the studies defended the continuity of use and the protection factor of RAAS blockers to the detriment of the other classes of antihypertensive drugs that do not modulate RAAS. It was found, then, that antihypertensive treatment should be maintained, as it does not worsen the prognosis in the face of Sars-CoV-2 infection. However, the studies are mainly observational and, therefore, cannot establish strong causal relationships. For this reason, robust randomized controlled trials are needed to better understand this topic.